Responsabilidad estatal del gobierno legislador en el marco del COVID-19 (2020)
The states of emergency by which an economic, social, and ecological emergency is decreed to address a global pandemic such as Covid-19, lead us to examine the response capacity of Colombia to avert a crisis with repercussions on the democratic, jurisdictional, and political systems. All of this, within the framework of unrestricted respect for human rights, since the main concern of law derives from the concentration of public powers in the executive branch and omitting the convening of a great national democratic dialogue within Congress to review and approve the solutions to the crisis through special legislation for these cases of pandemic, beyond exceptional decrees with long-term force of law protected by rules for short periods, which is burdensome for the rule of law, foreseeing that the Government, as legislator, covers many issues without adequate controls and without convening all the representative powers of the State. This article examines fundamental rights and controls, as well as the responsibility of the Legislating Government when it holds extra powers, and it finally addresses the objective imputation based on special harm in accordance with the mechanisms for the protection of the fundamental rights of the IACHR and human rights.